Strategi Pemasaran Terhadap Peningkatan Kinerja UMKM dimoderasi Teknologi pada masa Pandemi Covid-19 - Satria Tirtayasa; Ira Nadra; Hazmanan Khair (JURNAL ILMIAH MANAJEMEN & BISNIS, 2021)
The purpose of this study was to examine the impact of the marketing approach during the Covid-19 pandemic on the performance of MSMEs with technology as a moderating variable with the research subject in the Medan City Court Street workshop. This thesis uses an associative and quantitative analysis approach. The population of this research is all workshop entrepreneurs who are on the street of Medan Court. Saturated sample is the entire population of 100 respondents as the sample of this study. The data collection approach has been tested for validity and reliability by reporting, interviews, and questionnaires. The Structural Equation Model (SEM) method with the alternative method of Partial Least Square (PLS) is an analysis of the data used in this study. The results showed that: (1) With a value of 0.767 and a P-value of 0.0033, the effect of production on the performance of MSMEs is positive and significant. (2) With a result of 0.000 (0.05), technology moderates the impact of production on MSME performance positively and significantly. (3) production on the performance of MSMEs is positive and significant with a value of 0.468 and a P-Value of 0.042 (4). direct marketing to the performance of MSMEs with a value of -0.265 and a P-Value of 0.000. (6) the positive and significant effect of direct marketing on the performance of MSMEs, which is moderated by technology, shows the result of 0.000 (0.05).